Formation tracking of mobile robots under obstacles using only an active RGB-D camera - Guan, Renhe (2023)
This article attempts to achieve leader-follower formation tracking for mobile robots under obstacles with only one RGB-D camera on the follower. In contrast, most existing research employs at least two sensors, including a camera and a LiDAR. However, the limited field of view of RGB-D cameras introduces three significant challenges: 1) intermittent observation of the leader, 2) partial detection of obstacles, and 3) conflicting observations of the leader and obstacles. To overcome these difficulties, we first propose a controller that enables the follower to achieve continuous observation and formation tracking of the leader without obstacles and depth images. To address the partial detection of obstacles, we design a rotating device that allows the camera to actively extend its observation range and resolve conflicts with leader detection. Based on camera feedback and the proposed controller, a multiobjective controller is presented that enables the follower to achieve formation tracking and obstacle avoidance simultaneously, without requiring communication or leader velocity. Simulations and experiments are conducted to demonstrate the feasibility of our methods.